Immunohistochemical study on localization of serotonin immunoreactive cells in the gastrointestinal tract of the European catfish (Silurus glanis, L.). Issue 1 (21st July 2014) - Köprücü, S.; Yaman, M.
Summary: In this study, it was aimed to identify the distribution of serotonin immunoreactive cells within the gastrointestinal tract (GIT) of European catfish ( Silurus glanis ). For this purpose, the tissue samples were taken from the stomach (cardia, fundus and pylorus region) and intestine (anterior, middle and posterior region). They were examined by applying the avidin‐biotin‐immunoperoxidase method. The serotonin containing immunoreactive cells are presented in all regions of the GIT. It was determined to be localized generally in different distribution within the stomachs and intestines of S. glanis . It was found that the most intensive regions of immunoreactive cells were the cardia stomach and posterior of intestine.